An Analysis of Pragmatic Presupposition in Maturity Episode on Golden Ways Show - Sianipar, Maria Olivia Christina (Association of Language Teachers in Southeast Asia (ALTSA), 2020)
Pragmatics is concerned with the study of meaning as communicated by speaker or writer and interpreted by a listener or a reader. It has consequently more to do with the analysis of what people mean by their utterances. Describing the types of presupposition by the utterances in a talk show named Golden Ways is the objective of this research. The subject of this research is a talk show entitled maturity. The data are some utterances said by the speaker and heard by the hearer. Utterances between the host and the audiences from this show can show the presupposition. The writer analyzed the types of presupposition by Yule’s theory (1996) to find out what types are often used in this talk show. The data analysis is conducted by classifying and categorizing the data to find the inferences. The writer uses a descriptive method because it describes the presupposition in the talk show and it was suitable to the purpose of the study. As Monsen stated (2008: 5) the descriptive research often illustrates a relevant but non quantified topic involving a well-focused research question. It generates narrative data that describe words instead of numbers. The writer has found all six types of presupposition which applied in this talk show. This research shows that presupposition always exist in utterances.